DIFFICULTIES OF MOTOR COORDINATION OF SCHOOL OF 9 A 12 YEARS OLD. (Fiep Bulletin - online, 2014)
The difficulties of coordination of motor skills have been highlighted in the school age, being observed while writing, the class of physical education or sports. The goal of the study was to investigate the difficulties driving school aged between 09 and 12 years old. Part of this study 88 schools, randomly selected randomly, 50 male and 38 female. The instrument used in this study was the Movement Assessment Battery for Children-ABC Movement (Drums for the Evaluation of the Children's Movement-M-ABC; HENDERSON AND SUDGEN, 1992). The M-ABC has been specifically developed to identify and evaluate children with limitations of motor coordination. This instrument assesses the manual skills, skills of controlling object, static equilibrium and dynamic balance. According to the results, 22 schools had difficulty driving light and 13 difficulty severe motor, corresponding to 14.8% of the participants. When compared the results of the scores of swiftly manual skills of school, it was observed that there was no statistically significant difference (p = 0.168) between the male and female group. In carrying out with ball skills, the boys have been better than girls, and this difference statistically significant, with p
Keywords: Difficulties for the Motor Coordination; Motor Development; Scholars